Factors Affecting The Companies’ Preferences On Integrated Reporting - DURAK, Mustafa Gürol (International Journal of Contemporary Economics and Administrative Sciences, 2014)
The aim of this study is to reveal the factors affecting the companies’ preferences towards publishing integrated reports. By reviewing the literature, the factors are classified under two groups, namely; country-specific factors and firm-specific factors. The general results obtained from studies on integrated reporting shows that in countries where societal values prevail over individual values, where there is a high demand for information and where strong enforcement mechanisms exist, it is expected that companies are more likely to publish integrated reports. From a micro-level (firm specific) perspective, large and profitable companies with strong governance structure, whose Boards include diverse perspectives are accepted to be closer to integrated reporting.